KAJIAN CUSTOMER RELATIONSHIP MARKETING DALAM BISNIS RITEL - TAN, SEPTIAN SETIADI DWITANTRA (Universitas Katolik Widya Mandala Surabaya, 2013)
An understanding of the application of customer relationship marketing in retailing and customer relationship marketing implications of a retail company in Indonesia is very important. It is based upon the demands for companies that run a retail business in order to develop customer relationship marketing as a strategy to survive in the fierce competition. In tight business competition, the ability to deliver more value to customers becomes important capital. Customers will get a better value than shopping at a competitor, so there is an interest to choose the retail stores of the company as a place of purchase. Customer relationship marketing is an attempt to establish a relationship to obtain information in order to be a basic response to give more value to customers than competitors. Customer relationship marketing is also an effort to build relationships with customers, so there is an emotional bond customers to always choose to shop at stores owned by the retailer. This will be the advantage for retail companies is a difficult imitated by competitors.